Analisis Perilaku Jangkrik (Gryllus bimaculatus) Pada Simulasi Efek Polusi Cahaya - Kharisma Arum Utami; Murni Ramli (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2022)
Artificial lighting is considered light pollution that affects the physiology and behavior of insects. Morphological characteristics of field crickets (Gryllus bimaculatus) have compound eyes that are sensitive to specific colors. In this case, light has a major effect in influencing behavior described in two main behaviors, namely stridulation pattern behavior (singing) and movement patterns. This experiment aimed to determine the behavior of crickets to various types of light color and temperature changes in the environment as a simulation of the effects of light pollution. The experimental results showed an increase in the aggressiveness of the movement and the frequency of stridulation in blue light and when the ambient temperature increased.